(untitled) (Research, Society and Development, 2021)
Propouse: surgical teams sometimes neglect surgical glove perforation. The aim of this study was to determine the prevalence of sterile glove perforation in maxillofacial surgical procedures. Methods: Two studies were performed. The first one evaluated 200 pairs of surgical gloves (50 in each group) used by first, second, and third-year residents (R1,R2,R3). In the second study, 150 pairs of surgical gloves were evaluated: 100 pairs were used by a third-year resident, including 50 pairs in oral surgery procedures and 50 pairs in trauma surgeries, and 50 pairs of unused gloves were tested as control. The gloves were examined for perforations by filling them with water and testing for leaks. Results: In the first study, 29 pairs (19.3%) were perforated. Of the 50 pairs of control gloves, 7 pairs (14%) showed perforations on either side. The thumb and index finger and the right-hand (dominant hand) gloves, were the most frequently perforated sites. In the second study, 6% of the gloves in the control group, 6% of the gloves used in oral surgeries, and 10% of the gloves used in trauma surgeries showed perforations. The index finger and thumb were the most affected sites. Conclusion: The perforation rate was higher for the dominant right hand. In both studies, the frequency of perforation of unused gloves was significant, indicating the need for better quality control of the gloves evaluated in this study.